Parallel breaking characteristics of diode-bridge power electronic switch for DC circuit breaker. (June 2022) - Qu, Lu; Yu, Zhanqing; Zeng, Rong; Yan, Xin; Gan, Zhizheng; Huang, Yulong
Highlights: Power electronic switch module should be designed as the symmetrical structure, to reduce the circuit stray inductance value, thus reducing the withstand voltage stress when the power electronics devices turn off, and improve the current sharing characteristics of the parallel breaking. The driving characteristics and switching characteristics of parallel IEGT can be as consistent as possible by adjusting the driving capacitance, driving resistance and other parameters and symmetrical layout of the driving circuit, so as to reduce the switching inconsistencies of parallel IEGT and thus improve the current-sharing characteristics of parallel switching. In order to reduce the peak breaking current of buffer branches, the buffer resistance can be increased within a certain range, but factors such as rated voltage value of MOV, turn-off current value and stray inductance of the line should be considered comprehensively. In order to reduce the peak voltage of the power electronic switch module, the buffer capacitance can be increased within a certain range, but it should not be too high. The volume and cost should be considered comprehensively. With a certain switching energy, the current breaking capacity will decrease when di/dt is high, and the current-sharing characteristics of parallel power electronic devices will deteriorate. To verify the effectiveness of paralleling method of the power electronic devices that is suitable for DC breaking, two power electronic switch module in parallel is developed, and the breaking current test for 51.5kA is carried out, with biggest non-current sharing for four IEGT is 2.1kA and good flow consistency properties. The effectiveness of paralleling method of the power electronic devices that suitable for DC breaking is verified, laying the technical foundation for engineering applications of the power electronic switch suitable for DC breaking. Abstract: With the improvement of the breaking-current level of the DC circuit breaker, the current level of the existing power electronic devices cannot meet the demand of breaking the DC current. However, it can realize high-power DC breaking through the power electronic devices in parallel. In order to reveal the influencing factors and laws of parallel breaking characteristics of power electronic devices suitable for DC breaking, and to break through the parallel technology of power electronic devices suitable for DC breaking, the influence of stray inductance of power electronic switch branches, driving performance of power electronic devices, technical parameters of buffer branches and characteristics of switching current on the characteristics of parallel breaking are studied in this paper, which are based on the Injection Enhanced Gate Transistor (IEGT) and the diode bridge type topological structure of power electronic switches. And then a parallel method of power electronic devices suitable for DC breaking is proposed. Lastly, a power electronic switch module suitable for DC breaking is developed, and a parallel power electronic switch module test is carried out. The experimental results show that the two parallel power electronic switching modules can break 50kA current within 10 μs, and the maximum non-current sharing of the four IEGTS is 2.1kA. The current sharing characteristics are good, which verifies the effectiveness of the parallel method of power electronic devices suitable for DC breaking. The research results of this paper lay a technical foundation for the engineering application of power electronic switch suitable for DC breaking.